Earnings Management, Financial Distress, and Profitability: Does the Audit Committee Matter for Tax Aggressiveness? - Ruhani Ruhani; Rahma Yuliani; Monica Rahardian Ary Helmina (SAFE-Network, 2026)
This study aims to examine the effects of earnings management, financial distress, and profitability on tax aggressiveness, as well as the moderating role of the audit committee in the relationship between these variables and tax aggressiveness in coal mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employed a quantitative approach with an associative research design. The sample consisted of 17 companies selected using purposive sampling, resulting in 51 firm-year observations. Secondary data were obtained from the companies’ annual reports and financial statements and analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews software. The results indicate that earnings management has a positive and significant effect on tax aggressiveness, while financial distress has a negative and significant effect on tax aggressiveness. Profitability, however, has no significant effect on tax aggressiveness. Furthermore, the audit committee weakens the relationship between earnings management and tax aggressiveness but strengthens the relationship between financial distress and tax aggressiveness. Meanwhile, the audit committee does not moderate the relationship between profitability and tax aggressiveness. These findings highlight the importance of strengthening the effectiveness of the audit committee as a corporate governance mechanism to mitigate tax aggressiveness.